Per- and Polyfluoroalkyl Substances (PFASs) in Market Meats from Guangzhou, China: Age-Specific Dietary Exposure and Threshold Exceedance Risks - Yuting Qin; Yuhua Zhang; Hongfeng Zhang; Yan Li; Zhijun Bai; Yanyan Wang; Lili Huang; Weiwei Zhang (Journal of Food Protection)
Per- and polyfluoroalkyl substances (PFASs), known for their environmental persistence and adverse health effects, pose an elevated risk to vulnerable populations through dietary exposure. Yet, there is limited research on PFAS concentrations in market basket meats and offal from Guangzhou, China. We examined the distribution of 16 PFAS in 166 market basket samples (beef, pork, and offal (pork liver)) from Guangzhou. Age-specific dietary exposure and related health risk were assessed for 3–6-year-old children, 7–17-year-old adolescents, adults, and seniors, integrating local food consumption data and probabilistic risk models. The results demonstrated a variable distribution of PFAS based on food species, with offal exhibiting the highest level of contamination (mean Ʃ16PFAS: 6.209 ng·g−1). Perfluorooctanoic acid (PFOA) and perfluorooctanesulfonic acid (PFOS) were identified as the most predominant compounds contributing to dietary exposure of total PFAS. For the estimated weekly intake (EWI) of Ʃ4PFAS [PFOA, PFOS, Perfluorononanoic acid (PFNA), and Perfluorohexanesulfonic acid (PFHxS)] from meats and offal, the average EWI ranged from 3.252 to 5.710 ng·kg−1 body weight (bw) per week in four age groups. The probability of exceeding tolerable weekly intake (4.4 ng·kg−1 bw per week) is 51% in children, 45% in adolescents, and 39% in both adults and seniors. Offal was identified as the predominant source of the total PFAS exposure. This study provides the first insights into the age-specific health risk of PFAS from market meats and offal from Guangzhou, highlighting the urgent need for further research to establish safety benchmarks or consumption advisory values for these compounds in the Chinese diet.